Photopolymerization of hybrid monomers, Part II: Determination of relative quantum efficiency of selected photoinitiators in cationic and free-radical polymerization of hybrid monomers. (May 2018) - Nowak, Damian; Ortyl, Joanna; Kamińska-Borek, Iwona; Kukuła, Katarzyna; Topa, Monika; Popielarz, Roman
Abstract: A method for determination of relative initiation efficiency of free-radical photoinitiators directly in monomers by Fluorescence Probe Technique (FPT) has been expanded into cationic photoinitiators and the use of LEDs instead of monochromatic light sources. The relative initiation efficiency of a series of cationic photoinitiators relative to diphenyliodonium hexafluorophosphate, and a series of free-radical photoinitiators relative to 2, 2-dimethoxy-2-phenylacetophenone (Irgacure 651), in cationic and free-radical photopolymerization of 2-(2-vinyloxyethoxy)ethyl acrylate (VEEA) and 3, 4-epoxycyclohexylmethyl methacrylate (Cyclomer M100) hybrid monomers has been determined. It was found that the initiation efficiency of cationic photoinitiators does not depend on the type of monomer, while the type of monomer affects initiation efficiency of free-radical photoinitiators. Highlights: The FPT method for determination of relative initiation efficiency of photoinitiators is extended into cationic photoinitiators. Relative initiation efficiency of a series of photoinitiators in hybrid monomers has been determined for the first time. Effect of monomer on initiation efficiency of photoinitiators has been evaluated.